ANALISIS STRUKTUR, PERILAKU, DAN KINERJA PEMASARAN IKAN PATIN SALAI DI KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Rahmadani '; Novia Dewi; Eliza ' (Indonesian Journal of Agricultural Economics, 2016)
The research was conducted at November 2015 in processing center time after harvest Koto Mesjid village, Pulau Gadang village and in some market, the marketing purpose is Kuok market, and Air Tiris market. The purpose of the research was to know marketing path, market structure, market conduct, and market performance. Market structure approach are usingmarket share analysis, CR4 (Concentration Ratio for Biggest Four), Hirschman Herfindahl Index,and Barrier to Entry. Market conduct approach is using descriptif qualitatif analysis about the market that become research object. While market performance approach is using marketing margins analysis in this case based on the concept of the product reference.Respondent in this research was smoke catfish stake holder, and saleswith respondent totally 35 respondent people. This research used survey method. The result of this research showed that structure of market smoke catfish Pangasius Sutchi in Kampar regency at perfect market competition. Result of CR4 (Concentration Ratio for Biggest Four) showed that concentration rasio highest was retailer 34,64 % by IHH average 0,1242. Average value of Minimum Effisiency of Scale (MES) highest is 13,41 %. The marketingmargin value for distributor Rp 7.235/kg, for agency was Rp 7.778/kg and for retailer was Rp 12.250/kg.